Dynamic stress control of bi-material structure subjected to sawtooth shock pulse based on interface characteristics. (July 2020) - Zhang, Xiangyuan; Shi, Yao; Pan, Guang
Highlight: Influence factors of dynamic stress are investigated analytically. Tungsten carbide may increase the impact strength of aluminum structures. Polyamides may reduce the impact strength of the aluminum structure. Abstract: This paper focuses on dynamic stress control of bi-material structure under the action of sawtooth shock pulse. The factors that are likely to influence the dynamic stress are studied based on the analytical method. Then two bi-material models and a homogenous material model are investigated through the finite element method. The supplement of tungsten carbide layer could reduce the stress of aluminum alloy significantly are proposed here, while the supplement of polyamides layer, to some extent, enlarge the stress of aluminum alloy. It also suggests that the stress control is related to several key factors - the acoustic impedance, the Poisson's ratio, the ratio of thickness to width of material, the deformation and the wave frequency.